PERBANDINGAN POSITIVE YOUTH DEVELOPMENT SISWA YANG MENGIKUTI EKSTRAKURIKULER OLAHRAGA DAN TIDAK MENGIKUTI EKSTRAKURIKULER DI SMAN 97 JAKARTA - Hendra Lesmana, - (2020)
This study aims to determine the differences in the development of positive attitudes of students who take extracurricular sports and not take extracurricular activities. The research method used is quantitative comparative research, with a comparative causal design. The population in this study were 100 students of class X and XI, who took sports extracurricular activities and did not take extracurricular activities and the sample used was 40 students or female students of SMAN 97 Jakarta who were divided into 2 different groups. The instrument used was Positive Youth Development Inventory (PYDI) (Short version) and then analyzed by using the independent sample t-test. The result of this research is that there is a significance value of p (0.00) < 0.05, which means that there is a difference in the Positive Youth Development of students who take extracurricular sports at SMAN 97 Jakarta From the data obtained, it can be concluded that sports extracurricular activities have better positive youth development for students of SMAN 97 Jakarta who take sports extracurricular activities compared to students or students who do not take extracurricular activities . Keywords: Extracurricular, Extracurricular, Positive Youth Development, Positive Youth Development Inventory (Short Version), Students